EVALUASI MUTU PRODUK AKHIR TEH MAHKOTA DEWA (PHALERIA PAPUANA) DI PT. SALAMA NUSANTARA WATES KULON PROGO, YOGYAKARTA - , MATHEUS SABDO WIDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Good quality control system should be able to provide all the necessary information with a chart or table that can predict or estimate a final product. Examination of the raw materials is the basis of acceptance or rejection of materials offered by the seller and is good information to plan how to mix or sorting materials. Information obtained during the stages of the process indicates whether modifications are needed in the process. It is necessary to study the quality of the analysis to determine the quality of the production of crown god tea product is good or not. With this research is expected to provide an overview of production feasibility, especially in the final product crown god tea production PT. Salama NUSANTARA. This will help in evaluating the quality of production or the quality of the final product crown god tea. In this final project report that the main problem is the quality of the final product the gods crown in 2010. The quality of the final product seen from inaccuracies in weighing the crown god tea packaging products. Weighing inaccuracies obtained from the test by using the Map Control X and R. The test results will be compared with the results of the weighing company standards. The products are experiencing causes irregularities will be identified and made improvements possible companies to improve product quality. From the results of mapping the X and R. Weight Control X for green tea is not normal because there are three plots of data that is out of control. The cause of the abnormality of the weight due to assignable causes so that the necessary corrective action and improvement. By using CEDAC known that the biggest cause lies in humans and tools.